Needleless emulsion electrospinning for the regulated delivery of susceptible proteins - Buzgo, Matej; Filova, Eva; Staffa, Andrea Mickova; Rampichova, Michala; Doupnik, Miroslav; Vocetkova, Karolina; Lukasova, Vera; Kolcun, Radka; Lukas, David; Necas, Alois; Amler, Evzen (Journal of tissue engineering and regenerative medicine, 2018)
In the present work, we developed a novel needleless emulsion electrospinning technique that improves the production rate of the core/shell production process. The nanofibres are based on poly-ε-caprolactone (PCL) as a continuous phase combined with a droplet phase based on Pluronic F-68 (PF-68). The PCL-PF-68 nanofibres show a time-regulated release of active molecules. Needleless emulsion electrospinning was used to encapsulate a diverse set of compounds to the core phase [i.e. 5-(4,6-dichlorotriazinyl) aminofluorescein -PF-68, horseradish peroxidase, Tetramethylrhodamine-dextran, insulin growth factor-I, transforming growth factor-β and basic fibroblast growth factor]. In addition, the PF-68 facilitates the preservation of the bioactivity of delivered proteins. The system's potential was highlighted by an improvement in the metabolic activity and proliferation of mesenchymal stem cells. The developed system has the potential to deliver susceptible molecules in tissue-engineering applications.
Keywords: Animals; Swine, Miniature; mezibuněčné signální peptidy a proteiny; tkáňové podpůrné struktury; emulsion electrospinning; emulze; mezenchymální kmenové buňky; nanovlákna; biokompatibilní materiály; time-regulated release; Intercellular Signaling Peptides and Proteins; jehly; Collagen Type II; tkáňové inženýrství; Poloxamer; miniaturní prasata; needleless core/shell electrospinning; prasata; Nanofibers; Dextrans; Needles; dextrany; Proteins; Polyesters; Mesenchymal Stem Cells; Biocompatible Materials; growth factor; proteiny; Swine; Pluronic F-68; rhodaminy; Horseradish Peroxidase; kolagen typ II; Emulsions; Tissue Engineering; zvířata; poloxamer; polyestery; Tissue Scaffolds; křenová peroxidasa; Rhodamines